How is assessment with the Teaching at the Right Level (TaRL) Approach implemented in Science Learning? - Murniningsih Murniningsih; Ani Widyawati; Trisniawati Trisniawati; Nika Cahya Awani; Citra Ayu Maharani (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
The Teaching at the Right Level (TaRL) approach offers a solution through assessments that adapt learning based on student ability levels. This study aims to examine the implementation of TaRL-based assessments, identify obstacles encountered, and outline solutions used to overcome them. This study used a descriptive qualitative method with a deductive thematic analysis approach. The results showed that the TaRL assessment was implemented through two stages: diagnostic assessment (cognitive and non-cognitive) and formative assessment with differentiated worksheets (LKPD). Solutions implemented included group rotation, development of LKPD with varying difficulty levels, simple and contextual diagnostic assessments, and collaboration between teachers. This study concluded that the TaRL approach can be implemented effectively with the support of adaptive and collaborative strategies. The implication is that teachers need to have skills in designing assessments that are appropriate to students' abilities and strengthen collaboration within the teaching team so that this approach can run sustainably.